EMPOWERING WOMEN THROUGH READING LITERACY: A STUDY OF THE “IBU CERDAS BERDAYA” NON-PROFIT ORGANIZATION - Ratu Nuri Bonauli Hutagalung; Lydia Christiani (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
Despite Indonesia’s evolving digital landscape, women, especially housewives, often face literacy gaps that make them more vulnerable to information overload and gender issues. While non-profit digital communities have emerged as alternative hubs for literacy, their role in structured empowerment remains underexplored within the field of Library and Information Science (LIS). This study aims to analyze the process of women’s empowerment through literacy in the non-profit organization “Ibu Cerdas Berdaya” (commonly known as @bbbbookclub). Using a qualitative case study approach, data were collected through purposive sampling involving the founder and three active members, achieving data saturation through repetitive thematic dimensions. Data collection included semi-structured interviews, virtual observations, and document analysis of internal evaluation reports for triangulation. The collected data were analyzed using the Braun & Clarke's thematic model. The findings reveal that: (1) the implementation of systematic literacy programs, such as reading challenges, book discussions, and competitions, effectively transform social media into a Virtual Community of Practice (VCoP); and (2) this participation significantly shifts information behavior, enhancing critical information filtering and personal autonomy. “Ibu Cerdas Berdaya” plays a crucial role in enhancing the quality of life for Indonesian housewives and mitigating intellectual isolation among them  by bridging the gap between digital recreation and functional literacy. This community-driven model offers a valuable framework for empowering marginalized groups through information activities in the digital age.